PENGARUH TERAPI BERMAIN CLAY TERHADAP KECEMASAN HOSPITALISASI PADA ANAK USIA 3-6 TAHUN - Heny Nurmayunita; Apriyani Puji Hastuti (Jurnal Keperawatan Malang, 2019)
Introduction Hospitalization in children is a process for a reason that requires children to stay in the hospital, undergoing therapy and treatment until the child can be repatriated home. During the process, the child can experience various events in the form of a very traumatic and stressful experience. To address the problem of hospitalization of pre-school children aged 3-6 years can be administered with the play of Clay therapy. The study was made with the aim of knowing the therapeutic influence of playing Clay against hospitalization anxiety. Method This research uses Pre-experimental methods with One group Pre-Post test. Samples were chosen using the consecutive sampling technique with inclusion and exclusion criteria and sample of 20 people. The variables used in this study were the play therapy of Clay and the level of hospitalization anxiety. Data processing and data analysis using Test T test. Results Research shows that there is a therapeutic influence to play Clay against the hospitalization of children aged 3-6 years in the space Nusa Indah Hospital army Dr. Soepraoen Malang by Using Test T Test with a result of 0.000 which is less than < 0.05. The research is expected to provide feedback on the part of health services especially hospitals that have a child's space to provide Clay play therapy and other play therapies as one of the media to relieve anxiety Hospitalisation in children, especially age 3-6 years according to their age.